PERLINDUNGAN HUKUM BAGI KONSUMEN ATAS PRAKTIK TUKANG GIGI DI LUAR WEWENANG DI KABUPATEN KUTAI KARTANEGARA - Sari, Dewi Kumala; Susanti, Erna; Hediati, Febri Noor (Jurnal Ilmiah Advokasi, 2025)
The existence of traditional dental practitioners (tukang gigi) is often considered an alternative dental care option for lower-middle-class communities, although such practices are generally unlicensed and exceed the authority granted by law. This study aims to analyze two main issues: first, the forms of legal protection for consumers against unauthorized dental practices in Kutai Kartanegara Regency; and second, the legal remedies available to consumers harmed by such practices. This research applies a socio-legal approach, collecting empirical data through interviews with various parties, including traditional dental practitioners in Kutai Kartanegara Regency, consumers who suffered losses, the Kutai Kartanegara Health Office, the Consumer Dispute Settlement Agency (BPSK) of Samarinda City, and dentists who have treated patients previously handled by tukang gigi. The findings reveal that unauthorized dental practices, such as tooth filling, extraction, braces installation, and veneer application, can be classified as unlawful acts (onrechtmatige daad) under Article 1365 of the Indonesian Civil Code. These acts cause both material and immaterial losses to consumers, thereby requiring legal protection under Law No. 8 of 1999 on Consumer Protection and relevant civil law provisions. With effective protection mechanisms and legal remedies, consumers are expected to obtain legal certainty and fair accountability for the losses suffered.Keywords: Consumer Protection, Traditional Dental Practitioners, Unlawful Act, Liability.